Memory and funeral rites: an aproximation to the korean commu-nity in the Ciudad de Buenos Aires - Castiglione, Celeste (Instituto de Altos Estudios Sociales, 2017)
The Korean migration, residing in Argentina for 50 years, posseses a relationship with the traditions and the religious world that unravels in the numerous churches that establish in a part of the Flores neighbourhood in the Ciudad de Buenos Aires. This religious institutions have a polivalent function in the community, being a part of a complex net. In the present work we have focused in the articulation that establishes when one of the members perishes in the receptive society. To make this close up to such a delicate sphere of the individual, the family and the group, we consider that in-depth interviews give us an invaluable input. They allow us to work the narratives, the construction of the subjetivity and social representations that develop in a frame of interculturality, that’s crossed by a moment that’s so intimate as the death of one of its members. To that end we have shared encounters with members of different churches, ethnical leaders and associations with the objective of investigate about what it means for the community, with all the complexity that this carries (contextual, religious, generational and familiar, to quote some of them), honor and say goodbye to their loved ones on the other side of the world.